THE IMPORTANCE OF TEACHING FOREIGN LANGUAGE (ENGLISH LANGUAGE) TO CHILDREN IN SECONDARY SCHOOL. - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
This article discusses the benefits of teaching English as a foreign language to children at school age in today's globalized world. It highlights how learning English at a young age enhances cognitive development, promotes social and cultural awareness, provides long-term career advantages, and boosts self-confidence. The article emphasizes the importance of incorporating English language education into the curriculum of children to prepare them for the demands of a globalized world.